2020
DOI: 10.1136/ejhpharm-2020-002298
|View full text |Cite
|
Sign up to set email alerts
|

Severe and fatal medication errors in hospitals: findings from the Norwegian Incident Reporting System

Abstract: Background Even with global efforts to prevent medication errors, they still occur and cause patient harm. Little systematic research has been done in Norway to address this issue. Objectives To describe the frequency, stage and types of medication errors in Norwegian hospitals, with emphasis on the most severe and fatal medication errors. Methods Medication errors reported in 2016 and 2017 (n=3557) were obtained from the Norwegian Incident R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 22 publications
4
51
0
4
Order By: Relevance
“…Another study suggested that 63.6% of patients reported medication errors in acute care hospital settings [ 19 ]. Under-reporting or lack of emphasis on accurate medication error-reporting may be one of the major issues for the variation in the medication error rates [ 12 , 20 ]. Undoubtedly, low and inaccurate reporting of medication errors interferes with the identification and prevention of causes, limiting opportunities to improve patient safety by understanding and sharing knowledge on error detection and safe practices [ 11 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study suggested that 63.6% of patients reported medication errors in acute care hospital settings [ 19 ]. Under-reporting or lack of emphasis on accurate medication error-reporting may be one of the major issues for the variation in the medication error rates [ 12 , 20 ]. Undoubtedly, low and inaccurate reporting of medication errors interferes with the identification and prevention of causes, limiting opportunities to improve patient safety by understanding and sharing knowledge on error detection and safe practices [ 11 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some evidence has revealed that early-career nurses seek employment in nursing environments with a focus on quality patient care [ 33 , 34 , 35 ]. Despite the importance of error communication, the actual amount of error reporting is lower than the number of actual medication errors determined by experts [ 11 , 20 ]. Thus, understanding perceived barriers to error reporting, from the nurses’ perspective, is crucial in promoting reporting behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Avvikene ble rapportert uten risiko for sanksjoner. En gjennomgang av 3 372 legemiddelavvik som ble rapportert til meldeordningen i 2016 og 2017 (5), viste at 68 % av avvikene forekom ved utdeling, 24 % ved ordinering og 6 % ved istandgjøring. De vanligste avvikstypene var doseavvik (38 %), glemt legemiddel (23 %) og feil legemiddel (15 %).…”
Section: Fortolkningunclassified
“…Våre tall stemmer relativt godt overens med resultatene fra den forrige undersøkelsen (9), og også med det som ble rapportert til meldeordningen i årene 2016-17 (5). Selv om meldeordningen har mottatt rapporter fra rundt 60 ulike sykehus og vi kun har sett på ett, var det små forskjeller i andelen rapporter mellom studiene for sentrale avviksgrupper som doseringsavvik, at det var gitt et annet legemiddel enn ordinert og at legemidlet var gitt til en annen pasient.…”
Section: Tabellunclassified
See 1 more Smart Citation